Sustainability committee effectiveness and integrated reporting quality in the oil and gas industry `does corporate financial performance matter?' - Ally Adam Mshana (Cogent Business & Management, 2024)
This study investigates the relationship between sustainability committee (SC) effectiveness and integrated reporting (IR) quality in the global oil and gas industry, focusing on the moderating role of financial performance. Drawing on stakeholders' and legitimacy theories, this study hypothesises that SC effectiveness positively influences IR quality and that financial performance moderates this relationship. Using a sample of 500 firm-year observations from 100 companies listed in Forbes Global 2000 from 2018 to 2022, the findings reveal that SC effectiveness significantly enhances IR quality. Specifically, SC size and diligence are positively linked to higher IR quality. Although the direct effect of SC independence on IR quality is insignificant, it becomes significant when financial performance is considered a moderating factor. Interestingly, financial performance negatively moderates the relationship between SC effectiveness and IR quality, although this effect disappears when analysing individual SC components separately. These results highlight the complex interplay among SC effectiveness, financial performance, and IR quality, suggesting that companies should focus on enhancing SC size and diligence to improve reporting quality, particularly in financially constrained firms. Additionally, to harness the positive moderating effect of financial performance, companies should ensure that financial resources are strategically allocated to support the sustainability committee's activities and promote a holistic view of value creation, incorporating financial and non-financial aspects.
Keywords: 650; Sustainability committee effectiveness; integrated reporting quality; oil and gas industry; corporate financial performance; integrated reporting